THE INFLUENCE KAIZEN BEHAVIOR AND ORGANIZATIONAL COMMITMENTS ON, JOB SATISFACTION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN THE SIDOARJO STATION - Ak’yas Daksani Achmad (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
KAIZEN is one of Japan's proven methods to achieve the vision and mission of success in the business world and work in a particular agency, especially PT KAI. Organizational commitment is a form of obedience, priority and consistency in a particular organization, both vision and mission. The purpose of this research is to prove and analyze the effect of kaizen and organizational commitment on job satisfaction and organizational citizenship behavior (OCB) among PT KAI employees at Sidoarjo Station. This research was conducted using a quantitative approach, with samples analyzed namely 100 employees. the analysis technique used is the slovin formula using the SPSS 26 type of software. The results of this study indicate that each variable has a linear effect on the dependent variable. However, in other parts of the multiple regression shows no joint effect on the dependent variable Keywords: Kaizen Behavior, Organizational Commitments On, Job Satisfaction, Organizational Citizenship Behavior (OCB).